A perspective on value co-creation processes in eSports service ecosystems. Issue 1 (23rd December 2021) - Kunz, Reinhard E.; Roth, Alexander; Santomier, James P.
Abstract : Purpose: Electronic Sports (eSports) is an emerging sector of the sports and entertainment industry experiencing an accelerated increase in consumer and sponsor demand. This paper aims to study selected cases of eSports service ecosystems, to identify similarities and differences and to understand the different roles, relationships and multiple interactions of actors involved in value co-creation processes. Design/methodology/approach: This empirical paper follows the service-dominant logic to highlight value creation. Based on the sport value framework, an organizing logic for the actors in sports-related ecosystems to exchange service and co-create value, the authors apply the conceptualization of an eSports service ecosystem framework in which actors create value through their interactions. A case study approach was applied to qualitatively describe two cases of value co-creation by multiple actors during three eSports events. Case study 1a is the 2019 League of Legends World Championship Finals in Paris. Case study 1b is the 2020 League of Legends World Championship Finals in Shanghai. Case study 2 is the BLAST Premier Counter-Strike: Global Offensive Global Final 2020, which was entirely virtual. Findings: The outcome is an empirically investigated conceptual framework of multiple actors co-creating value within a service ecosystem in eSports. The insights of the cases explain how actors interact with each other and co-create value during events in eSports ecosystems. The cases illustrate interactions in the context of eSports where the actors are connected within ecosystems. This enables further development of a value co-creation concept and a better understanding of value co-creation in eSports. Originality/value: This study contributes to research by explicating a theoretically grounded framework for eSports service ecosystems based on empirical evidence. This research extends the scope of value co-creation beyond the firm–customer dyad to a service ecosystem in eSports, demonstrating the dynamic interactions of multiple actors.